Using V. Voskobovich's Game Technology in Kindergar-Ten as a Basis for Creating a Psychologically Comfortable Developing Environment - Grigorenko E. N., Pogretskaia M. G., Shnareva I. A., Serbina I. E. (Psychologically Safe Educational Environment: Design Problems and Development Prospects, 2020)
this article introduces a unique gaming technology in its capabilities “Fairy mazes of the game”, as well as a system of developing of logical and mathematical representations and skills based on the use of games by V. Voskobovich.
Keywords: игровая технология; умственные способности ребенка; творческие способности ребенка; логико-математические игры; открытия; game technology; child's mental abilities; child's creative abilities; logical-mathematical games; discoveries